Characterization of Radiation Modified Sago-Polyvinyl Alcohol Blends Films - Idris, Sarada (2008)
Blends from sago starch, poly (vinyl alcohol)(PVA) and distilled water have been prepared and subjected to electron beam irradiation with doses ranging from 10 to 40 kGy to form hydrogels. The hydrogels were then cooled in refrigerator overnight to remove trapped bubbles formed during irradiation reaction. Films were subsequently produced by drying hydrogels in an oven. The characteristic of the irradiated blends and films were then determined. Poly (vinyl alcohol) solution was found to be viscous obviously after irradiation indicated the formation of irradiation induced crosslinking. Radiation degradation of sago starch solution was confirmed by observing the viscosity of the solution which was lowered after irradiation. The gel content of irradiated films was increased compared to unirradiated. Crosslinking/grafting had occurred in the blends at optimum dose of 20 kGy. The gel content of poly (vinyl alcohol) film was maximum at 30 kGy. Above 30 kGy, over crosslinking occurred as the film was shrunk to the smaller size. Melting temperature of PVA film as determined by Differential Scanning Calorimetry decreased with increasing irradiation dose. This indicate that cross linking had lowered the melting point of PVA film. The existence of only one peak of melting temperature by Thermo Gravimetric Analysis revealed the compatibility of the blends. Scanning Electron Miscroscopy studies on the surface morphology and freeze fracture revealed more evidence of the radiation induced crosslinking and grafting of the blends. Studies also done on effect of sago and PVA contents of the blend, addition and types of plastisizers added and irradiation dose on the quality of the film produced. Results show that irradiation has improved the tensile strength but elongation at break was slightly reduced for blends S25/P75, S50/P50 and S75/P25. The biodegradability of sago, PVA and blends films was studied by monitoring its weight loss for 6 months. Sago starch film was totally degraded in the first month of burial period but PVA film remain un intact for the last six months. Incorporating sago starch to the blend sago-PVA improved the weight loss up to 60% in six months.